Macroeconomic determinants of Malaysian housing market - Ong, Tze San; Chang, Yee Shan (ORIC Publications, 2013)
House price of Malaysia has experienced significant price expansion over the past few years and became a worrying trend for lenders currently. This study is an attempt to identify the macroeconomic determinants of house prices in Malaysia from year 2000 until middle of 2012. The study also explores the relationship between the characteristics and house price then will forecast the house price index for the next 3 years. There are total of three macroeconomic variables such as inflation rate, gross domestic product rate and income increment rate were taken into study with the house price index. The design of this study comprises of 50 secondary data of each variables from year 2000 until middle of year 2012 which are in quarterly basis. In the process of findings, there are few types of analysis were tested by using SPSS Version 20.0, there are Pearson correlation coefficient, multiple regression analysis, multicollinearity statistics and finally scenario analysis to forecast the future trend of house price index in next three years. The result indicates that there are not all predictors in this study are significantly related to house price, but only gross domestic product rate is significant determinants of the movement of house price index. The overall study intends to contribute and enhance both investors and government execution on scenario planning that have relationship upon the unpredictable rise of house price. This study will also help home buyers to assess the timing from macroeconomic factor to purchase their house. This study might be different from other country as the findings proved that the performance of house price in Malaysia is generally caused by the growth of economic that is gross domestic product rate.